A lírica fragmentária de Ana Cristina Cesar: autobiografismo e montagem - Souza, Carlos Eduardo Siqueira Ferreira de (2008)
The main objective of this research is to examine, in the writings of Ana Cristina Cesar, the relationships between the texture of her autobiographical discourse and the cinematic editing method, with particular attention to the texts comprised in A teus pés, published in 1982. Such objective was chosen in view of the fact that Ana Cristina Cesar s poetic work reveals composition methods of a singular late 20th century lyrical voice, marked by a fragmentary language, analogous with the cinematic technique of frames juxtaposition and the procedures that account for autobiographical and confessional texts. In order to understand how this woman poet appropriates an autobiographical discourse and transforms it, and whether the cinematic language takes part in the autobiographical construction process of Ana Cristina s poetry through the organization of fragments in the text, we start from the following hypotheses: autobiographism is a lyrical and fictional method in Ana Cristina s fragmentary poetry; cinematic editing provides solutions to the contiguity of analogical images in her poetic writing; fragmentarism is the procedure that brings together the cinematic and the autobiographical discourse. Such hypotheses were tested in the light of: Bakhtin s reflections in Aesthetics of Verbal Creation, which deal with confessional and autobiographical genres; the concept of biographeme as proposed by Roland Barthes; and the cinematic editing studies carried out by theoreticians and scholars such as Sergei Eisenstein, Ismail Xavier, Peter Burger and Modesto Carone Netto. We conclude that Ana Cristina Cesar brings together the depragmatizing, self-reflexive tendency of modern art and the disillusioned, faithless attitude of our contemporary age, by deconstructing in her writings the concepts of identity and authorship, in an attempt to depersonalize the self. In the texts written by this woman poet from Rio de Janeiro, the biographeme is apprehended as a fragmentary and non-linear composition method which, together with the frames juxtaposition procedure that constitutes cinematic editing, results in a unique relationship between reality and fiction, achieved by means of an erotic texture in which a reality that emerges and disappears from the text is displayed. Bringing forth a dramatic interplay in which the poetic persona takes to the stage and displays its multiplicity to the reader, Ana Cristina Cesar s writing reveals that the theatralization of the self on the textual stage is an alternative to the invention of a creative and liberating identity